2022
DOI: 10.48550/arxiv.2201.06069
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering a new universal partizan ruleset

Abstract: In Combinatorial Game Theory, we study the set of games G, whose elements are mapped from positions of rulesets. In many case, given a ruleset, not all elements of G can be given as a position in the ruleset. It is an intriguing question what kind of ruleset would allow all of them to appear. In this paper, we introduce a ruleset named turning tiles and prove the ruleset is a universal partizan ruleset, that is, every element in G can occur as a position in the ruleset. This is the second universal partizan ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Early results showed that generalized konane and turning tiles are universal partizan ruleset ( [2,4]). In this study, we will use the latter ruleset.…”
Section: Universal Partizan Rulesetmentioning
confidence: 99%
“…Early results showed that generalized konane and turning tiles are universal partizan ruleset ( [2,4]). In this study, we will use the latter ruleset.…”
Section: Universal Partizan Rulesetmentioning
confidence: 99%
“…The notion of a universal ruleset is defined in [1], and the same paper proves that Generalized Konane is a universal ruleset. The ruleset that was secondarily shown to be universal is Turning Tiles and since then, two other rulesets were also shown to be universal by (polynomial-time) reductions from Turning Tiles [4,5]. The universality of a game implies that it is sufficiently complex.…”
Section: Introductionmentioning
confidence: 99%